Short circuit study of a balanced 3 phase system using p-inverse - Sabbir, Hasan Muhommod; Rashed, Md. Imam Hossain (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015